DIFFERENTIAL EFFECT OF SCHOOL TYPE ON RESEARCH COMMITMENT AMONG POST-GRADUATE STUDENTS IN THE SOUTH-EAST OF NIGERIA - Jeremiah, Ebeh Jideofor (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Research is an integral part of the post-graduate program in any given academic field in Nigeria's education ecosystem. However, there is growing concern about the declining commitment toward research works among students enrolled in the graduate program in the university system. Although, previous research has identified the constraints impeding the realization of positive research attitudes in the higher education ecosystem. The primary objective of the current paper is to test the differential effect of school type on research commitment among post-graduate students in southeast Nigeria. Ninety-six students enrolled in graduate programs in the private and public universities in the Enugu and Ebonyi States of Nigeria completed a self-report measure. The mean, standard deviation score, and t-test result indicated a statistically significant difference between the two groups on research commitment. Thus, the result indicated that graduate students in the private university are more committed to research work than their counterparts in the public university.